American College of Rheumatology Guidance for the Management of Pediatric Rheumatic Disease During the COVID‐19 Pandemic: Version 1. Issue 11 (28th September 2020) - Wahezi, Dawn M.; Lo, Mindy S.; Rubinstein, Tamar B.; Ringold, Sarah; Ardoin, Stacy P.; Downes, Kevin J.; Jones, Karla B.; Laxer, Ronald M.; Pellet Madan, Rebecca; Mudano, Amy S.; Turner, Amy S.; Karp, David R.; et al.
Abstract : Objective: To provide clinical guidance to rheumatology providers who treat children with pediatric rheumatic disease (PRD) in the context of the coronavirus disease 2019 (COVID‐19) pandemic. Methods: The task force, consisting of 7 pediatric rheumatologists, 2 pediatric infectious disease physicians, 1 adult rheumatologist, and 1 pediatric nurse practitioner, was convened on May 21, 2020. Clinical questions and subsequent guidance statements were drafted based on a review of the queries posed by the patients as well as the families and healthcare providers of children with PRD. An evidence report was generated and disseminated to task force members to assist with 3 rounds of asynchronous, anonymous voting by email using a modified Delphi approach. Voting was completed using a 9‐point numeric scoring system with predefined levels of agreement (categorized as disagreement, uncertainty, or agreement, with median scores of 1–3, 4–6, and 7–9, respectively) and consensus (categorized as low, moderate, or high). To be approved as a guidance statement, median vote ratings were required to fall into the highest tertile for agreement, with either moderate or high levels of consensus. Results: The task force drafted 33 guidance statements, which were voted upon during the second and third rounds of voting. Of these 33 statements, all received median vote ratings within the highest tertile of agreement and were associated with either moderate consensus (n = 6) or high consensus (n = 27). Statements with similar recommendations were combined, resulting in 27 final guidance statements. Conclusion: These guidance statements have been generated based on review of the available literature, indicating that children with PRD do not appear to be at increased risk for susceptibility to SARS–CoV‐2 infection. This guidance is presented as a "living document, " recognizing that the literature on COVID‐19 is rapidly evolving, with future updates anticipated.